THE INFLUENCE OF SPIRITUAL COMPETENCE AND LEADERSHIP ON THE RELIGIOUS CULTURE OF STUDENTS IN PAI-BP LEARNING IN GRADE VIII SMP NEGERI 2 TAKALAR - Syaikhah Fakhrunnisa Abubakar; Saprin; Ulfiani Rahman (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
The declining religious character among students today is a concern that calls for serious attention from educational institutions. Teachers of Islamic Religious Education and Character Development (PAI and BP) are expected not only to deliver subject content but also to become role models with strong spiritual awareness and leadership. Unfortunately, these two essential competencies are still not fully reflected in daily school practices. This study aims to examine how the spiritual competence and leadership competence of PAI and BP teachers influence the religious culture of eighth-grade students at SMP Negeri 2 Takalar. A quantitative approach was employed using an ex post facto design. Data were gathered through Likert-scale questionnaires and documentation from 171 student respondents and analyzed using descriptive and inferential statistics, including simple and multiple linear regression. Findings reveal that both the spiritual and leadership competencies of teachers are perceived as low by the majority of students. Likewise, the students' religious culture is also categorized as low. Statistically, spiritual competence contributes 23.2%, leadership competence 32.5%, and both combined contribute 34.5% to students' religious culture. The study concludes that teachers play a vital role in shaping students' religious character. Therefore, strategic efforts are needed to strengthen these competencies through teacher training and school-based development programs.